Ethanol, Methanol, and Magnesium-Treated Palm Kernel Shell Biochar for Methylene Blue Removal: Adsorption Isotherms - Nur Hanani, Hasana; Rafeah, Wahi; Yusralina, Yusof (IJCRR, 2021)
ABSTRACT Introduction: Biochar’s adsorbent attributes, for instance, surface area, porous structure, surface functionality, and adsorption capacity, can be enhanced via suitable chemical modification. Objective: This work aimed to study the effect of ethanol (EtOH), methanol (MeOH), and magnesium (Mg) treatment on adsorbent properties of palm kernel shell (PKS) biochar. Methods: The PKS biochar was obtained through fast carbonization in a rotary kiln (800 ºC, 10 min) followed by steam activation (8 h). Both the EtOH and MeOH treated biochar were afforded via EtOH and MeOH treatment of PKS biochar, respectively, in the presence of HCl (6 h), followed by rinsing, filtering, and oven-drying. Mg treated biochar was obtained by soaking the PKS biochar with MgSO4 .7H2O at 30 ºC for 60 h. The EtOH, MeOH, and Mg treated biochars were characterized via proximate analysis, functional group analysis, surface area, and pore volume analyses. A batch adsorption study was conducted for adsorption of methylene blue (MB) by each EtOH, MeOH, and Mg treated biochar, respectively. Results: Brunauer–Emmett–Teller (BET) analysis indicated that carbonization and chemical treatment has successfully enhanced the surface area with raw PKS (0.848 m2g-1), PKS biochar (592 m2g-1), EtOH-treated biochar (647 m2g-1), MeOH-treated biochar (663 m2g-1), and Mg-treated biochar (674 m2 g-1). Batch adsorption studies showed that the highest methylene blue (MB) removal percentage for all studied biochar occurred at an initial concentration of 7 ppm (PKS biochar: 93.12%, EtOH-treated PKS biochar: 94.79%, MeOH-treated PKS biochar: 95.79%, and Mg-treated PKS biochar: 98.51%). Conclusion: The EtOH, MeOH, and Mg treated PKS biochar gave high MB removal and thus, could potentially serve as efficient adsorbents for removal of dyes from wastewater.